A mechanistic model of a PWR-based nuclear power plant in response to external hazard-induced station blackout accidents - Liu, Tao; Wu, Zeyun; Bensi, Michelle; Ma, Zhegang (Frontiers in Energy Research, 2023)
Natural hazard-induced nuclear accidents, such as the Fukushima Daiichi Accident that occurred in Japan in 2011, have significantly increased reactor safety studies in understanding nuclear power plant (NPP) responses to external hazard events such as earthquakes and floods. Natural hazards could cause the loss of offsite power in NPPs, potentially leading to a Station Blackout (SBO) accident that significantly contributes to the overall risk of NPP accidents. Despite the fact that extensive research has been conducted on the SBO accident for NPP, further understanding of these events is needed, particularly in the context of the dynamic nature of external hazards such as external flooding. This paper estimates the progression of SBO events for a generic pressurized water reactor (PWR) in response to external flooding events. The original RELAP5-3D model of the Westinghouse four-loop design PWR was adopted and modified to simulate the external flood-induced SBO accident, including the short-term and long-term SBO scenarios. A sensitivity analysis of long-term SBO, examining reactor operation times and analyzing key parameters over time, was also conducted in this work. The results of the analyses, especially the critical timing parameters of key event sequences, provide useful insights about the time during the external flooding event, which is important for plant operators to make timely decisions to prevent potential core damage. This paper represents significant progress toward developing an integrated risk assessment framework for further identifying and assessing the effects of the critical sources of uncertainties of NPP under external hazard-induced events.